Tradisi Kecil di Lingkungan Muslim: Sebuah Peta Islamisasi di Kendal - Ismawati Ismawati (Refleksi: Jurnal Kajian Agama dan Filsafat, 2004)
This writing discusses the mapping of the results of the Islamization process by scholars in Kendal, a district adjacent to Semarang, the capital of Central Java. Despite the efforts of reform initiated by Kendal’s own scholars who sought knowledge in Mecca, especially in the 19th and 20th centuries, traces of pre-Islamic customs still persist among the common people and have not been completely eradicated. This article reveals the religious practices among the supporters of small traditions within the Muslim community in Kendal.